2014
DOI: 10.2527/jas.2014-6874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of demographic factors and information sources on United States consumer perceptions of animal welfare

Abstract: As consumers have become more interested in understanding how their food is produced, scrutiny and criticism have increased regarding intensified food animal production methods. Resolution of public concerns about animal agricultural practices depends on understanding the myriad factors that provide the basis for concerns. An online survey of 798 U.S. households was conducted to investigate relationships between household characteristics (demographics, geographic location, and experiences) and level of concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
115
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 23 publications
17
115
1
3
Order By: Relevance
“…However, judgments of trustworthiness are also affected by the extent to which individuals or organisations are perceived to be transparent about their practices (Peters et al 1997;Fisman and Khanna 1999;Maeda and Miyahara 2003;Rawlins 2008). This may explain why animal-protection groups are considered more credible sources of information than are livestock industry groups (McKendree et al 2014), and why this positive perception increases following animal-abuse scandals (Scudder and Bishop-Mills 2009;Tiplady et al 2013). These results are consistent with other research, showing that whistle-blowers are viewed favourably by society (Callahan and Dworkin 2000), despite the short-term upheaval caused by exposés (Hersh 2002).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…However, judgments of trustworthiness are also affected by the extent to which individuals or organisations are perceived to be transparent about their practices (Peters et al 1997;Fisman and Khanna 1999;Maeda and Miyahara 2003;Rawlins 2008). This may explain why animal-protection groups are considered more credible sources of information than are livestock industry groups (McKendree et al 2014), and why this positive perception increases following animal-abuse scandals (Scudder and Bishop-Mills 2009;Tiplady et al 2013). These results are consistent with other research, showing that whistle-blowers are viewed favourably by society (Callahan and Dworkin 2000), despite the short-term upheaval caused by exposés (Hersh 2002).…”
supporting
confidence: 82%
“…This resistance is likely to be increased as a result of the reputational damage already suffered by the livestock industries. Animal-advocacy organisations are seen as more trustworthy sources of information than are animal industries (McKendree et al 2014), and this difference in credibility is magnified in the wake of animal-abuse exposés when attitudes towards the livestock sector are especially negative (Tiplady et al 2013). This may explain why negative press has a much greater impact on consumer behaviour than has any positive effect from advertising (Verbeke and Ward 2001).…”
Section: Educate the Publicmentioning
confidence: 92%
“…Industrial efficiency was viewed negatively and invariably led to more traditional, smaller and lower intensity farms being preferred. In quantitative studies, the majority of participants reported being concerned about FAW, with the proportion ranging between 46 and 86 % (McKendree et al 2014;Bennett and Blaney 2003), more commonly towards the higher end of this range. Those who viewed contemporary farming practices more positively were more appreciative of modern production, with benefits like more sanitary conditions, greater efficiency and improved welfare cited.…”
Section: Attitudes Towards Welfarementioning
confidence: 99%
“…When discussing specific aspects of FAW these often had a human motivation, such as the reduction of the risk of disease transfer and veterinary residues. Behaviour 14-51 % of study participants reported intending to, or already having, decreased their consumption of animal products (McKendree et al 2014;Ellis et al 2009). The restriction of certain meat types were more common than others, with pork and beef consumption most likely to decrease, and chicken consumption most likely to increase, although this may well be due to health and safety concerns, not just welfare considerations.…”
Section: Anthropocentric Versus Zoocentric Concernsmentioning
confidence: 99%
“…This type of disagreement is likely to be frustrating for both sides and unhelpful in the development and implementation of welfare improvements" [4]. Wolf et al [1] and McKendree et al [5] found evidence that demographic factors, such as gender, age, income, and experience with aspects of animal welfare influenced views on livestock animal production processes. Thus, understanding how demographic and other factors potentially influence perceptions of dairy cattle production processes may be important to ensure that dairy farm decision-making is keeping with public expectations.…”
Section: Introductionmentioning
confidence: 99%